Inhibitory effects of high extracellular l-glutamate concentrations on skeletal myogenesis - Himiko Ban; Koji Nobe; Soushi Kobayashi (Scientific Reports)
Abstract l-glutamate (Glu) is accumulated abundantly in skeletal muscle cells and plays a central role in energy production, amino acid metabolism, and protein synthesis. If intracellular Glu leaks due to plasma membrane fragility or injury, it may adversely affect the surrounding myocytes. In the present study, we examined the effects of high extracellular Glu concentration on skeletal myogenesis. Five mM Glu stimulation decreased the expression of fast-twitch myosin heavy chain isoforms and myogenin, an indicator of C2C12 cell differentiation into myocytes, and inhibited the cell fusion. This stimulation reduced the expression of metabotropic glutamate receptor 5 (mGluR5) and N-methyl-d-aspartate receptor 1 (NMDAR), which are glutamate receptors on the C2C12 plasma membrane. Furthermore, phosphorylation of p38 mitogen-activated protein kinase, myocyte enhancer factor 2A, and cAMP response element binding protein, which are downstream of these Glu receptors, was reduced, and the expression of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) decreased. Moreover, reduced mGluR5 and NMDAR expression and muscle weight were observed in the tibialis anterior muscle of mice with increased aging markers. These findings provide insights into the molecular mechanisms contributing to age-related muscle fragility and highlight the potential detrimental effects of elevated Glu on muscle health.